Do Antitakeover Provisions Spur Corporate Innovation? A Regression Discontinuity Analysis - Chemmanur, Thomas J.; Tian, Xuan (Journal of financial and quantitative analysis, 2018)
We study the effect of antitakeover provisions (ATPs) on innovation. To establish causality, we use a regression discontinuity approach that relies on locally exogenous variation generated by shareholder proposal votes. We find a positive, causal effect of ATPs on innovation. This positive effect is more pronounced in firms that are subject to a larger degree of information asymmetry and operate in more competitive product markets. The evidence suggests that ATPs help nurture innovation by insulating managers from short-term pressures arising from equity markets. Finally, the number of ATPs contributes positively to firm value for firms involved in intensive innovation activities.